Study of some factors affecting the incidence of veining defect in thighs destined to dry-cured process of Parma ham - Russo V.; Lo Fiego D.P.; Nanni Costa L.; Tassone F. (5. International Symposium on the Mediterranean Pig, 2007)
The veining defect is usually localized under the skin on the medial side of the thigh. The defect appears some hours after pig death, becomes particularly visible during ham trimming and is still evident after the dry-curing process. The assessment of the veining defect is made by a photographic scale which leads to a more precise and constant evaluation at trimming. Results of this study show an increase of veining incidence with carcass leanness. Moreover, the frequency of veining defect is affected by the stunning method of pigs and by the time that the thighs are not refrigerated after being separated from the carcass (pre-chilling time). The frequency of this defect increases with CO2 compared to the electronarcosis stunning, and with prolongued pre-chilling time.
5. International Symposium on the Mediterranean Pig, 2004/09/16-19, Tarbes (France)